Lo normativo como espacio de esperanza. Reflexiones en torno a Lucas E. Misseri, Derecho, justicia y utopía. Una perspectiva iusfilosófica de la literatura utópica - Martínez Mesa, Francisco José (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
In Derecho, justicia y utopía, Lucas Misseri addresses the close relationships between these three concepts, especially from the founding moment of modern utopia, with the publication of Utopia by Thomas More in 1516. The emancipatory, humanist and critical components contained in it configure an anthropological vision that clearly connects with the ideals and commitments of Law, especially in the contemporary world. His analysis will be developed from the paths of development and diffusion of utopianism, the literary one, through which he explores the course of the relationships between human aspirations for a better life and the role and evolution of the normative instruments created to regulate their coexistence.